Dynamic Course of Pulmonic Valve Endocarditis Resulting in Submassive PE and Valve Replacement - Chloe Grace Meyer BS; Thomas Paul Vacek MD; Amit Bansal MD; Ravi Gurujal MD; Analkumar Parikh MD (SAGE Publishing, 2018)
This report illustrates a case of a 42-year-old male with a history of intravenous drug abuse who presented with septic shock. Diagnostic studies, including a transthoracic echocardiogram, chest computed tomography angiography, transesophageal echocardiogram, and blood cultures ultimately revealed Serratia marcescens pulmonic valve infective endocarditis that was treated with intravenous antibiotics. In addition to the rare form of endocarditis and bacterium involved, this case brings into awareness the dynamic nature of the hospital course that requires vigilance in responding to hypotensive episodes for consideration of pulmonary embolism. Surgical valve replacement was opted for due to such a complication in addition to the large size of the vegetation, 2.5 cm.